Unusually rapid growth of brown tumour in the mandible after parathyroidectomy associated with the presence of a supernumerary parathyroid gland - Dorigatti de Ávila, Érica [UNESP]; De Molon, Rafael Scaf [UNESP]; Cabrini Gabrielli, Marisa Aparecida [UNESP]; Hochuli-Vieira, Eduardo [UNESP]; Sgavioli Massucato, Elaine Maria [UNESP]; De Mello-Filho, Francisco Veríssimo [UNESP]; Conti, Luis Carlos [UNESP]; Real Gabrielli, Mário Francisco [UNESP] (Elsevier, 2012)
The aim of this study is to report the case of a quick growing brown tumour in the jaw after a parathyroidectomy due to the presence of a rare fifth parathyroid gland. The patient had chronic renal disease and the diagnosis was tertiary hyperparathyroidism. Thirty days after the parathyroidectomy, the patient returned with a significant increase in the tumour size. The suspicion of a supernumerary gland was confirmed by parathyroid scintigraphy. The treatment of brown tumour is dependent on the treatment of the hyperparathyroidism. However, curettage should be considered if a large lesion is disturbing mastication. In conclusion, this case should attract the attention of general practitioner dentists, since they may be the first professionals who have contact with the patient with a brown tumour in the jaws. Likewise, this case emphasises the importance of knowing the type of hyperparathyroidism involved to allow for effective treatment planning. © 2011 European Association for Cranio-Maxillo-Facial Surgery.
Keywords: Brown tumour; Mandibular mass; Tertiary hyperparathyroidism; 25 hydroxyvitamin D; alkaline phosphatase; calcium; colecalciferol; parathyroid hormone; phosphorus; sevelamer; tracer; vasodilator agent; adult; alkaline phosphatase blood level; anemia; blood chemistry; blood pressure regulation; bone cyst; bone development; bone lesion; brown tumor of mandible; calcium blood level; canine tooth; case report; chronic kidney disease; computer assisted tomography; curettage; dialysis; differential diagnosis; dysphagia; face asymmetry; general anesthesia; giant cell; giant cell granuloma; hemodialysis; histopathology; hormone substitution; human; hyperparathyroidism; hypocalcemia; hypoparathyroidism; iliac bone; male; mandible; mandible tumor; mediastinum; molar tooth; palate; parathyroid hormone blood level; parathyroid hyperplasia; parathyroid scintiscanning; parathyroidectomy; phosphate blood level; premolar tooth; rib; skull; speech disorder; sternoclavicular joint; tertiary hyperparathyroidism; thymectomy; thyroparathyroidectomy; tooth root; tumor biopsy; tumor growth; tumor volume; vitamin supplementation; whole body scintiscanning; Granuloma, Giant Cell; Humans; Hyperparathyroidism, Secondary; Male; Mandibular Diseases; Osteitis Fibrosa Cystica; Parathyroid Glands; Parathyroidectomy; Postoperative Complications; Renal Insufficiency, Chronic; Young Adult